Trichloroisocyanuric Acid Mediated Oxidative Dehydrogenation of Hydrazines: A Practical Chemical Oxidation To Access Azo Compounds - Su, Yingpeng; Liu, Xuan; Yu, Jie; Cao, Guiyan; Zhang, Rong; Zhao, Yanan; Huang, Danfeng; Wang, Ke-Hu; Huo, Congde; Hu, Yulai (Synthesis, 2020)
A highly efficient, metal-free, chemical oxidation of hydrazines has been implemented using environmentally friendly TCCA as oxidant. This benign protocol provides straightforward access to a wide range of azo compounds in THF in excellent yield. Altogether, 35 azo compounds were obtained in this way and scale-up preparations were performed. Additionally, a plausible mechanism was also proposed. Step-economical process, mild reaction conditions, operational simplicity, high reaction efficiency, and easy scale-up highlight the practicality of this methodology.
Keywords: trichloroisocyanuric acid; dehydrogenation; hydrazines; azo compound; chemical oxidation